3D video and its applications - Matsuyama, Takashi.
3D video technology is the latest innovation in information media technology. This comprehensive text/reference presents a broad review of state-of-the-art 3D video production technologies and applications. The book opens with a concise introduction to the field, before examining the geometric, photometric, and dynamical design and calibration methods for multi-view camera systems, including practical implementation technologies. A range of algorithms are then described for producing 3D video from the video data captured by these systems. A selection of 3D video applications are also demonstrated. Topics and features: Describes real-time synchronized multi-view video capture, and object tracking with a group of active cameras Discusses geometric and photometric camera calibration, and 3D video studio design with active cameras Examines 3D shape and motion reconstruction, texture mapping and image rendering, and lighting environment estimation Demonstrates attractive 3D visualization, visual contents analysis and editing, 3D body action analysis, and data compression Highlights the remaining challenges and the exciting avenues for future research in 3D video technology Developed from more than 15 years of the authors’ research in the field, to inspire others working in this fascinating area This informative text will be of great benefit to graduate students and junior researchers wishing to understand the world of 3D video. Introduction -- Part I: Multi-view video capture -- Multi-camera systems for 3D video production -- Active camera system for object tracking and multi-view -- Part II: 3D video production -- 3D shape reconstruction from multi-view video data -- 3D surface texture generation -- Estimation of 3D dynamic lighting environment with reference -- Part III: 3D video applications -- Visualization of 3D video -- Behavior unit model for content-based representation and edition of 3D video -- Model-based complex kinematic motion estimation -- 3D video encoding.